1975
DOI: 10.1002/1097-0142(197508)36:2<458::aid-cncr2820360222>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in brothersCase reports and a review of 30 cases of male breast cancer

Abstract: Two brothers with breast cancer are presented. One died 8 years after diagnosis and the other is presently living a t 1 year with metastatic disease. T h e courses of 28 other previously unreported male patients with carcinoma of the breast are reviewed, and the possibility of male breast carcinoma being metastatic disease from the prostate is discussed. Useful etiologic information might be obtained from following the offspring of male breast cancer patients to see if they are a t increased risk of developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Most authors found no association of prostatic cancer and breast cancer (Keller, 1967;Mabuchi et al, 1985;Schottenfeld et al, 1963). In contrast, in studies other than case-control studies, several investigators have mentioned a possible association between prostate cancer and male breast cancer (Choudhury et al, 1982;Marger et al, 1975;Schlappack et al, 1986;Sobin and Sherif, 1980). Sobin and Sherif (1980) found a worldwide correlation between the incidence of these 2 tumours, and this is confirmed in our data.…”
Section: Analytical Epidemiologysupporting
confidence: 85%
See 2 more Smart Citations
“…Most authors found no association of prostatic cancer and breast cancer (Keller, 1967;Mabuchi et al, 1985;Schottenfeld et al, 1963). In contrast, in studies other than case-control studies, several investigators have mentioned a possible association between prostate cancer and male breast cancer (Choudhury et al, 1982;Marger et al, 1975;Schlappack et al, 1986;Sobin and Sherif, 1980). Sobin and Sherif (1980) found a worldwide correlation between the incidence of these 2 tumours, and this is confirmed in our data.…”
Section: Analytical Epidemiologysupporting
confidence: 85%
“…Although some authors state that lobular carcinoma cannot occur in men because male breasts do not contain lobules (Alagaratnam et al, 1981;Axelsson and Andersson, 1983;Meyskens et al, 1976;Ramantanis et al, 1980), several cases of lobular carcinoma have been reported (Bernheim et al, 1985;Sanchez et al, 1986;Tschahargane et al, 1985;Yogore and Sahgal, 1977). An estimated 1 to 5% of patients have bilateral tumours (Alagaratnam et al, 1981;Allain et al, 1988;Coley et al, 1971;Cordiano et al, 1971;Holleb et al, 1968;Marger et al, 1975;Moss, 1964;Peltokallio and Kalima, 1969;Ramantanis et at., 1980;Treves and Holleb, 1955;Von Magyar et al, 1982;Yap et al, 1979). Paget's disease, a known pre-malignant condition for women, also predisposes to male breast cancer (Gupta et al, 1983;Lancer and Moschella, 1982;Moshakis et al, 1983;Satiani etal., 1977).…”
Section: Dressedmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare instances of families have been reported in which several men have developed breast carcinoma 12, 22–25. A higher incidence of breast carcinoma has been noted in Jewish males 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to heat and electromagnetic radiation, causing testicular damage and further leading to the development of MBC is also postulated [ 25 , 26 ]. An inherited predisposition for breast cancer is noticed in males-analogous to that in females [ 27 - 31 ]. A positive family history of a first-degree female relative having breast cancer is seen in up to 15–20% patients [ 32 ].…”
Section: Methodsmentioning
confidence: 99%